STRATEGI KEPALA SEKOLAH DALAM PENINGKATAN MUTU MADRASAH (STUDI PADA MADRASAH IBTIDAIYAH NEGERI 1 KOTA PRABUMULIH) - Lidya, Elva (Jurnal Ilmiah Bina Manajemen, 2018)
This study is conducted in Madrasah Ibtidaiyah Negeri I Prabumulih city, and object of the were in strategic of headmaster  deep increase quality the madrasah. Data Analysis with usefull technic SWOT Analysis. Result of Analysis indicate that is headmasters strategic deep increase quality of madrasah mentioned strategic, be based on result degree issue usefull Litmus Test with result : S-O score value is 32 issue strategic, W-O score value is 31 issue strategic, S-T score value is 30 issue strategic, and W-T score value is 27 issue moderate. It can be concluded that the classification of strategy issues is: utilizing extracurricular activities (non-academic) to increase achievement in the academic field, achievement in the field of religion, and achievement in the field of tahfidz homes that are linked to the socio-cultural surrounding communities as an effort to promote Prabumulih State 1 Madrasah Ibtidaiyah. Then the importance of implementing a learning process that is safe, comfortable, interesting and fun through interactive learning media by utilizing the cultural conditions of students, cultivating 5 work cultures of the ministries of religion and elements of 5 S ( greeting, polite, smile, respectful, well behaved) in providing excellent service to school committees, guardians of students and the community caring for education in the environment around madrasas, improving facilities and infrastructure through the role of committees and communities concerned with education. Nextin formulating madrasah quality improvement strategies programs, good cooperation between madrasas, committees, communities and the government is needed to improve its strategic programs.